Systematic Management of Character-Based Arts Extracurricular Activities: A Multiple Case Study of Academic Achievement Enhancement in Indonesian Elementary Schools - Pipin Sulastri; Ayi Najmul Hidayat (Journal of Innovation and Research in Primary Education, 2026)
Character-based arts extracurricular activities represent promising interventions for holistic student development, yet limited research examines their systematic management and relationship to academic achievement in resource-constrained elementary school contexts. This study investigated the management practices of character-based arts extracurricular activities and their influence on student academic achievement in two Indonesian elementary schools. Employing a qualitative descriptive case study design, data were collected through semi-structured interviews with school administrators, teachers, and parents; systematic observations of extracurricular activities; and document analysis of program materials and evaluation reports at SDN Citamiang 1 and SDN Karang Tengah in Sukabumi City. Thematic analysis examined management practices across planning, organizing, implementing, and evaluating dimensions. Both schools demonstrated systematic management approaches integrating character education within arts instruction through experiential learning, explicit reflection practices, and stakeholder collaboration. Students participating consistently for two or more semesters showed enhanced academic performance and character development in discipline, responsibility, and teamwork. Implementation challenges included qualified instructor shortages and material resource constraints, addressed through community partnerships, creative pedagogical adaptations, and enhanced parent engagement. Systematic management of character-based arts extracurricular activities effectively facilitates character development and academic achievement enhancement despite resource limitations. Findings provide replicable models for schools seeking to implement integrated arts-character programs while highlighting the importance of sustained participation, institutional adaptability, and multi-stakeholder collaboration for program success.